The treasury analysis based on the financial rates, a method of assessing the profitability and efficiency of the economic agents - ŢURLEA, Eugeniu; GEORGESCU, Floarea (Annals of Spiru Haret University. Economic Series, 2011)
The main objective of each firm is to achieve an increased profitability, by determining the quantity of the profit. This indicator is not sufficient to assess the degree of efficiency, profitability or business profitability. It becomes useful, therefore, through the determination of the financial rates, as these companies provide information about the direction towards the business moves. The financial rates are tools through which firms can make a series of tests and may also determine which strategies to pursue in order to achieve certain objectives. Based on these considerations, the purpose of this study is to determine a number of financial rates specific to the company treasury, having as a reference point the cash flow statements, and to perform an analysis on the obtained results.